2017
DOI: 10.1158/1538-7445.sabcs16-s6-07
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S6-07: Double blinded validation study to assess performance of IBM artificial intelligence platform, Watson for oncology in comparison with Manipal multidisciplinary tumour board – First study of 638 breast cancer cases

Abstract: Background: IBM Watson for Oncology (WFO) developed in collaboration with Memorial Sloan Kettering Cancer Centre is a cognitive computing system able to extract structured data from free text documents using natural language processing (NLP). It is a technology platform that uses NLP and machine learning to reveal insights from large amounts of unstructured data. Currently WFO provides treatment options only for breast, lung and colorectal cancers. In the present study we try to evaluate concord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…Cancer: Somashekhar et al demonstrated that the IBM Watson for oncology would be a reliable AI system for assisting the diagnosis of cancer through a double-blinded validation study. 19 Esteva et al analysed clinical images to identify skin cancer subtypes. 20 …”
Section: Overview Of the Medical Artificial Intelligence (Ai) Researcmentioning
confidence: 99%
“…Cancer: Somashekhar et al demonstrated that the IBM Watson for oncology would be a reliable AI system for assisting the diagnosis of cancer through a double-blinded validation study. 19 Esteva et al analysed clinical images to identify skin cancer subtypes. 20 …”
Section: Overview Of the Medical Artificial Intelligence (Ai) Researcmentioning
confidence: 99%
“…However, published works describing WFO do not report relevant statistical (eg, discrimination, calibration) and clinically oriented (eg, net benefit type) performance metrics. Instead, they focus on concordance (true positive rate where the ground truth is provided by physician—that is, the proportion of instances where WFO’s recommendation agrees with that of the treating physician363738). We recommend the following guidance for researchers to avoid such pitfalls:…”
Section: Critical Questionsmentioning
confidence: 99%
“…Farina et al experienced the control of the offline man-machine edge, which applies the release timings for the spinal motor neurons for controlling the prosthesis of the upper limb. IBM Watson for the oncology diagnosis can be a consistent AI for cancer diagnosis from start to the end, which was explained by Somashekhar et al [46] by a double-blinded validation study. A clinical image was examined for recognizing skin cancer subtypes [20].…”
Section: Artificial Intelligence (Ai) Applications In Healthcare Systemmentioning
confidence: 94%